Self-switching Diodes as RF Rectifiers: Evaluation Methods and Current Progress - Farhani Zakaria, Nor; Rizal Kasjoo, Shahrir; Mohamad Isa, Muammar; Zailan, Zarimawaty; Khairuddin Md Arshad, Mohd; Taking, Sanna (Institute of Advanced Engineering and Science, 2019)
In the advancement of the Internet of Things (IoT) applications, widespread uses and applications of devices require higher frequency connectivity to be explored and exploited. Furthermore, the size, weight, power and cost demands for the IoT ecosystems also creates a new paradigm for the hardware where improved power efficiency and efficient wireless transmission needed to be investigated and made feasible. As such, functional microwave detectors to detect and rectify the signals transmitted in higher frequency regions are crucial. This paper reviewed the practicability of self switching diodes as Radio Frequency (RF) rectifiers. The existing methods used in the evaluation of the rectification performance and cut-off frequency are reviewed, and current achievements are then concluded. The works reviewed in this paper highlights the functionality of SSD as a RF rectifier with design simplicity, which may offer cheaper alternatives in current high frequency rectifying devices for application in low-power devices.